2017
DOI: 10.1038/srep40009
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels are associated with obesity but not cardio-cerebrovascular events in Chinese inpatients with type 2 diabetes

Abstract: We aim to explore the associations between serum uric acid (SUA) and obesity and cardio-cerebrovascular events (CCEs) in Chinese inpatients with type 2 diabetes mellitus (T2DM). 2 962 inpatients with T2DM were stratified into quartile based on SUA concentrations. There were significant increases in the prevalence of both obesity (32.6%, 41.9%, 50.1%, and 62.8%, respectively, p < 0.001 for trend) and severe obesity (0.4%, 0.6%, 0.8%, and 1.3%, respectively, p < 0.001 for trend) across the SUA quartiles. A fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 42 publications
(78 reference statements)
3
54
1
Order By: Relevance
“…Obesity in the last decade become a global problem and has been recognized as a risk factor with a variety of clinical conditions and adverse health consequences; hyperuricemia is one of these conditions [ 28 ]. Nowadays, obesity and hyperuricemia and its complications, such as metabolic syndrome and cardiovascular diseases, have raised serious concern for public health in the international community because of their high prevalence, health consequences and substantial economic burden [ 21 ]. Several epidemiological studies have assessed the relationship between SUA and obesity in different population; however, to our knowledge, this is the first study that focused on SUA and obesity for the Bangladeshi population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity in the last decade become a global problem and has been recognized as a risk factor with a variety of clinical conditions and adverse health consequences; hyperuricemia is one of these conditions [ 28 ]. Nowadays, obesity and hyperuricemia and its complications, such as metabolic syndrome and cardiovascular diseases, have raised serious concern for public health in the international community because of their high prevalence, health consequences and substantial economic burden [ 21 ]. Several epidemiological studies have assessed the relationship between SUA and obesity in different population; however, to our knowledge, this is the first study that focused on SUA and obesity for the Bangladeshi population.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Wang et al [ 15 ] reported a positive relationship between BMI and SUA levels among healthy individuals in Jiangsu province of China. In more recent studies, a significant positive relationship was observed between SUA levels and obesity in population of China [ 21 , 22 , 23 , 24 ], Japan [ 25 ], India [ 7 , 26 ], Pakistan [ 27 ] Iraq [ 28 ] and United States [ 43 ]. Although a positive association between obesity and SUA levels has been reported in previous studies; the mechanism by which how uric acid is increased in obesity has not well elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, several previous studies have also shown the relationship between BMI and uric acid (Han et al 2018). For example, Chen et al (Chen et al 2017) also found that prevalence of obesity steadily increased across SUA quartiles in T2DM. A 10-year follow-up study demonstrated that BMI had a significant independent association with uric acid in all race-sex-groups (Rathmann et al 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Numerous factors, including poor diet, genetic predisposition, restricted physical activity, and advancing age, contribute to this rise in obesity, which indicates that obesity is a multifactorial disease [4][5][6]. Obesity can give rise to serious health complications, such as cardiocerebrovascular disease, fatty degeneration of the kidneys and liver, weight overload on joints and bone, and obesity-related type 2 diabetes [7][8][9]. Obese patients who have type 2 diabetes experience abnormal glucose regulation, abnormal lipid metabolism, and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%